Nucleic-acid recognition interfaces: How the greater ability of RNA duplexes to bend towards the surface influences electrochemical sensor performance - Tavallaie, R.; Darwish, Nadim; Brynn Hibbert, D.; Justin Gooding, J. (The Royal Society of Chemistry, 2015)
The influence of RNA versus DNA on the performance of electrochemical biosensors where redox-labelled nucleic acid duplexes bend towards the electrode surface has been assessed. Faster electron transfer was observed for duplexes containing RNA, suggesting duplexes with RNA are more flexible. These data are of particular importance for microRNA biosensors.